The influence of safety knowledge and safety motivation towards safety behavior on a liqufied petroleum gas company employees - Vijan, Devadas (2020)
This study was focused on company X where the company safety was lagging in terms of employee’s safety behavior and has been influenced by safety knowledge and safety motivation. This study aim was to understand how the elements of knowledge and motivation can affect the safety behavior of company X employees. The objectives of this research were to determine the level of safety behavior among company X employees, to examine the relationship between the elements of safety knowledge, and motivation on safety behaviour and to investigate the influence of safety knowledge and motivation on safety behaviour. The study was conducted using quantitative method where questionnaire form was used to collect data from 150 respondents. The questionnaire form was made up of total 18 items and divided into four categories namely, safety knowledge, safety motivation, safety compliance and safety participation. The questionnaire forms were distributed to the respondents’ and received back on the same day. The data received from the respondents’ were statistically analysed with the use of SPSS system. The result revealed that safety knowledge has a more positive relationship on safety compliance. Whereas, safety motivation has a more positive relationship with safety participation. Although the variables have established positive relationship, it still considered as moderate level of influence. Both company X management and workers need to cooperate each other to create employees with higher safety knowledge, safety motivation and safety behavior so any unwanted incidents can be prevented in future.